2006
DOI: 10.1177/0731684406063550
|View full text |Cite
|
Sign up to set email alerts
|

Melt Elasticity Phenomenon of Multicomponent (Talc and Calcium Carbonate) Filled Polypropylene

Abstract: The compound of single-component filled polypropylene (PP) (consists of either talc or CaCO 3 ) and multicomponent filled PP (talc/CaCO 3 /PP) are prepared by melt mixing using Brabender Plasticorder internal mixer. All systems exhibit good stability and normal flow in the molten state. The multicomponent filled PP has shown an intermediate degree of die swell and flow instabilities. The defect of extrudate in the extrusion process in the form of melt fracture could only be evidenced in the semisolid state of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…From a careful examination of the data in Figure 1, it appears that the reduction of PP/kaolin composites is continuous until a plateau level is attained at kaolin content of 25 php. This can be interpreted as a result of decreased entanglement of polymer molecules as reported by several investigators [12][13]. On loading the extruder's hopper with PP matrix, the PP starts to melt and as the mixing of matrix and filler continues, the viscosity of PP melt is reduced until it is believed to be fully melted.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…From a careful examination of the data in Figure 1, it appears that the reduction of PP/kaolin composites is continuous until a plateau level is attained at kaolin content of 25 php. This can be interpreted as a result of decreased entanglement of polymer molecules as reported by several investigators [12][13]. On loading the extruder's hopper with PP matrix, the PP starts to melt and as the mixing of matrix and filler continues, the viscosity of PP melt is reduced until it is believed to be fully melted.…”
Section: Resultsmentioning
confidence: 59%
“…Nonetheless, this fact can only be applied to UPVC/kaolin system as PP/kaolin system shows normal flow even if kaolin concentration is added up to 30 php in the PP system. In the investigations of melt elasticity of PP composites done by Ariffin et al [12] using talc and calcium carbonate as fillers, it has been concluded that filler is capable of preventing from the appearance of flow instability in PP composites. When the external force is released from the system, the presence of filler has delayed the movement/interaction of polymer molecules and decelerated the elastic recovery.…”
Section: Flow Instability Studies -Effect Of Kaolin Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…In conjunction, the ability of the lower viscosity melt to recover to its original position is easier than the highly viscous melt. Because the relaxation process of the highly viscous polymer melt is restricted, this will cause the melt injection pressure for the true viscosity data to generate higher shear stress .…”
Section: Resultsmentioning
confidence: 99%
“…These materials, which at the process temperature consist of suspensions of rigid particles in a viscoelastic liquid (the polymer melt), generally exhibit a very complex rheological behavior, which has been the subject of many theoretical and experimental studies . Part of these aimed at investigating their behavior in capillary flows at high shear rates, but the attention was rarely focused on the region close to the onset of flow instabilities .…”
Section: Introductionmentioning
confidence: 99%